Connection between gold dissolution in thiosulfate leaching and Cu(II) complexes during the cathodic process. (20th December 2019) - Nie, Yanhe; Yang, Lei; Wang, Qiang; Shi, Changliang; Zi, Futing; Yu, Hong
Abstract: The effect of the reduction half reaction of Cu(II) complexes on passivation and gold dissolution in the copper-ammonia-thiosulfate system were studied using electrochemistry and density functional theory (DFT). The results show that the cathodic process accounts for the surface passivation, aside from contributions made by thiosulfate decomposition during the anodic process. Copper sulfide and polysulfide are formed in the passivation layer during the reduction half reaction of Cu(II) complexes. The addition of common additives, such as ethylenediamine (EN) and ethylenediamine tetraacetic acid (EDTA), are able to not only remove the passive layer but also change the Cu(II) reduction half reaction. Tafel curves show that the gold leaching current in the EDTA-supplemented solution is higher than that in the EN-supplemented solution. Linear sweep voltammetry demonstrated that the reduction half reaction of Cu(II) complexes is controlled by the diffusion process, and the diffusion coefficient of the Cu(II) complex in the EN-supplemented solution and EDTA-supplemented solution is 0.64 × 10 −6  cm 2 /s and 1.44 × 10 −6  cm 2 /s, respectively. Density functional theory (DFT) studies showed that the lowest unoccupied molecular orbital (LUMO) of the mixed Cu(II)-ammonia-EDTA complex has lower energy than that of the mixed Cu(II)-ammonia-EN complex. Additionally, gold atoms on the surface that adsorbed the Cu(II)-ammonia-EDTA complex have higher relaxation degrees than those in the Cu(II)-ammonia-EN complex system. This explains why the gold concentration in the EDTA-supplemented solution is higher than that in the EN- supplemented solution. This study provides insight into the differences in gold dissolution during the cathodic process.